IPTEKS TEKNOLOGI INFORMASI TERHADAP PROSES AUDITING DAN PENGENDALIAN INTERNAL PADA PT. BANK SULUTGO - Arunde, Intan F.; Ilat, Ventje (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
The rapid development of Technology and Information has a very beneficial impact on PT. Bank SuluGo in conducting audits. The use of computers in modern times has an important role in corporate governance to achieve goals in the field of business. The purpose of this study is to determine the role of Information Technology in the audit at PT. SulutGo Bank. The role of Information Technology can facilitate auditors in completing work in their respective fields and can develop the performance of auditors and develop the ability of auditors to their respective primers in completing their work.Keywords : Internal Audit, Information Technology (IT), Internal Control